Models for Managing Secrets - Steele, J. Michael (Management Science, 1989)
Some elementary probability models are given that help articulate the trade-offs involved in managing secrets. One of these models captures the notion that the likelihood of disclosing a secret increases as the square of the number of people who are aware of it. Also, several classes of countermeasures are examined to determine their ability to increase the time window during which a secret can be held. One model suggests that disinformation countermeasures offer a promising technique for conserving secrets.